2020
DOI: 10.1212/nxg.0000000000000399
|View full text |Cite
|
Sign up to set email alerts
|

MYORG -related disease is associated with central pontine calcifications and atypical parkinsonism

Abstract: ObjectiveTo identify the phenotypic, neuroimaging, and genotype-phenotype expression of MYORG mutations.MethodsUsing next-generation sequencing, we screened 86 patients with primary familial brain calcification (PFBC) from 60 families with autosomal recessive or absent family history that were negative for mutations in SLC20A2, PDGFRB, PDGBB, and XPR1. In-depth phenotyping and neuroimaging investigations were performed in all cases reported here.ResultsWe identified 12 distinct deleterious MYORG variants in 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…Parkinsonism with vertical nuclear gaze palsy was uncommon in MYORG mutation carriers, but occurred in case 4, thus, extending the phenotypic spectrum of MYORG-related PFBC. Parkinsonism with vertical nuclear gaze palsy was reported to be associated with pontine calcifications, which were also noticed in the brain CT of case 4 (Chelban et al, 2020). In our study, homozygous or truncating mutations of MYORG could be associated with a more severe phenotype, such as in case 1 and case 4.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Parkinsonism with vertical nuclear gaze palsy was uncommon in MYORG mutation carriers, but occurred in case 4, thus, extending the phenotypic spectrum of MYORG-related PFBC. Parkinsonism with vertical nuclear gaze palsy was reported to be associated with pontine calcifications, which were also noticed in the brain CT of case 4 (Chelban et al, 2020). In our study, homozygous or truncating mutations of MYORG could be associated with a more severe phenotype, such as in case 1 and case 4.…”
Section: Discussionsupporting
confidence: 73%
“…We screened a total of 245 Chinese subjects including 21 subjects from 10 possibly autosomal recessive families and 224 sporadic cases. Eight MYORG variants were identified in six sporadic cases, while four of the eight variants were previously reported (c.103A > G, p.M35V; c.782_783GC > TT, p. R261L; c.1092_1097delCTTCGA, p.365_366delFD; and c.1967T > C, p. I656T) (Supplementary Figures S1A-D) (Yao et al, 2018;Forouhideh et al, 2019;Chelban et al, 2020;Chen et al, 2020). Notably, four novel variants in MYORG were identified: two nonsense variants (c.442C > T, p. Q148*; c.972C > A, p. Y324*) and two missense variants (c.1969G>C, p. G657R; c.2033C > G, p. P678R) (Figures 1A-D).…”
Section: Myorg Variants In the Primary Familial Brain Calcification Cohortmentioning
confidence: 92%
“…A detailed laboratory examination did not show significant difference between the cases. Interestingly, the pontine calcification (observed in Case 1, 4, 5) was not detected in our two SLC20A2 cases, in line with the literature (Nicolas et al 2013a, b); Chelban et al (2020) reported that pontin calcification on head CT may refer to MYORG mutation. These two cases point out that involvement of the same gene, partly depending on the different site of mutation, may also have different phenotypes.…”
Section: Discussionsupporting
confidence: 91%
“…Reads alignment using the hg19 human genome reference, variant calling and annotation were performed as described previously. 21 All cases were screened and were negative for known HSP-related genes.…”
Section: Genetic Analysismentioning
confidence: 99%